"MUD Play": A Transformative Learning Context - Regina O. Smith; Patricia L. Farrell (Adult Education Research Conference, 2001)
This case study describes Multi-user domains (MUDS) as a virtual learning environment for fostering the imaginative and symbolic aspects of transformative learning by relying primarily on the work of Boyd and Freire. MUDs are an increasingly popular but largely unexplored location for adult learning.